1982
DOI: 10.1016/0014-5793(82)81081-8
|View full text |Cite
|
Sign up to set email alerts
|

A new candidate for the regulation of erythropoiesis

Abstract: The effect of pure human insulin-like growth factor I (IGF I) on the colony formation of late stage erythroid precursor cells (CFU-e) from fetal mouse liver and adult bone marrow was studied in a serumfree culture system. We found that IGF I in physiological concentrations stimulated erythroid colony formation. The combined effect of IGF I and erythropoietin was smaller than the sum of their single effects. The number of colonies induced by IGF I was linearly dependent on the number of plated cells. Our result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(37 citation statements)
references
References 20 publications
1
35
1
Order By: Relevance
“…This observation is in apparent discordance with previously published data, 5,8,[17][18][19][26][27][28][29][30][31] and could be partially explained by the fact that in our study we have been cloning bone marrow CD34 + cells, depleted from hematopoietic accessory cells. These latter cells could secrete KL or IL-3 and/or other factors which can co-stimulate growth of the BFU-E colonies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This observation is in apparent discordance with previously published data, 5,8,[17][18][19][26][27][28][29][30][31] and could be partially explained by the fact that in our study we have been cloning bone marrow CD34 + cells, depleted from hematopoietic accessory cells. These latter cells could secrete KL or IL-3 and/or other factors which can co-stimulate growth of the BFU-E colonies.…”
Section: Discussioncontrasting
confidence: 99%
“…Several reports suggested that INS and/or IGF-I are required to costimulate with EpO erythroid colony formation in serum-free cloning medium. 5,8,[17][18][19][26][27][28][29][30][31] Nevertheless, we were not able to reproduce this observation when CD34…”
Section: Erythroid Colony Formation In Serum-free Inssupplemented Cumentioning
confidence: 99%
See 1 more Smart Citation
“…Cell culture assays for Ep are also sensitive to such factors (1, [8][9][10][11][12][13]. The observed effect varies with the culture system used, indicating that these factors may influence erythropoiesis in different ways and at various stages of differentiation (8,14).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, it stimulates the proliferation of a wide variety of cultured cells that are primarily of mesodermal origin (3)(4)(5). In addition, it can cause some cells to differentiate including chondrocytes (6), myoblasts (7), osteoblasts (8) and erythroid precursors (9). In vivo, IGF-I regulates postnatal skeletal growth (5,10).…”
Section: Introductionmentioning
confidence: 99%